Digestibility of animal ingredients for tambaqui and Nile tilapia - Sousa, Geisiane Silva; Bomfim, Marcos Antonio Delmondes; Nascimento, Daphne Cardoso Nagib do; Marchão, Rafael Silva; Ribeiro, Felipe Barbosa; Siqueira, Jefferson Costa de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective – This study aimed to determine the protein, energy, and phosphorus digestibility of animal ingredients (meat and bone, fish, blood, feather, and viscera meals) in diets for tambaqui (Colossoma macropomum) and Nile tilapia (Oreochromis niloticus).Methodology – A total of 48 tambaqui and 48 Nile tilapia were used, with a mean weight of 198.15 ± 3.11 g and 134.89 ± 2.22 g, respectively. The experiment followed a completely randomized design with a factorial arrangement (ingredient × species), comprising 10 treatments (five ingredients × two species), 3 temporal replications, and 8 fish per experimental unit.Originality/Relevance – This study simultaneously compared the digestibility of five animal meal ingredients for two key species of Brazilian aquaculture, namely tambaqui and tilapia, under a combined experimental protocol. This approach yielded standardized and directly comparable data, which are scarce in the literature. The practical relevance is high, as the digestibility coefficients obtained can be directly applied in feed formulation, contributing to cost reduction, improved feed efficiency, and simplified diet formulation for multispecies systems.Results – Tambaqui showed a higher apparent digestibility coefficient (ADC) for crude protein in fish meal (87.20%), whereas tilapia achieved higher ADCs for crude protein in meat and bone meal (85.43%), fish meal (86.38%), and viscera meal (85.92%). Regarding the ADC of gross energy, tilapia performed best with meat and bone meal (89.69%), whereas tambaqui exhibited higher ADC values for meat and bone (82.77%), fish (85.01%), and viscera (86.04%) meals. Both species showed the highest ADC of total phosphorus in blood meal. Furthermore, the species exhibited similar phosphorus ADC values for fish meal (68.42%), blood meal (90.36%), feather meal (55.68%), and viscera meal (60.01%). In practical terms and considering a few exceptions, the same digestibility coefficients of animal meal ingredients can be adopted for both species, given that significant differences were observed only in crude protein digestibility for blood and viscera meals.Theoretical/Methodological Contributions – This study provided updated digestibility coefficients for crude protein, gross energy, and phosphorus in animal meal ingredients used in diets for tropical fish. It demonstrated that, with few exceptions, mean values can be applied to both tambaqui and tilapia, thereby simplifying feed formulation in polyculture systems. The factorial design adopted herein, with two species × five ingredients and three temporal replications, ensured the statistical robustness and reliability of the results.Social and Environmental Contributions – The research contributes to feed efficiency and cost reduction in aquaculture, benefiting small- and medium-scale farmers by improving production planning and predictability. Furthermore, it supports environmental sustainability by reducing nutrient discharge and encouraging the utilization of animal industry co-products, fostering a circular economy in the aquaculture sector.
Keywords: Colossoma macropomum; Animal meal; Oreochromis niloticus; Nutritional value